Surface topography evolvement of galvanized steels in sheet metal forming - 侯英岢 于忠奇 张卫刚 蒋浩民 林忠钦 (Transactions of Nonferrous Metals Society of China, 2009)
U-channel forming tests were performed to investigate the surface topography evolvement of hot-dip galvanized（Gl） and galvannealed（GA） steels and the effects of die hardness on sheet metal forming（SMF）. Experimental results indicate that the surface roughness values of the two galvanized steels increase with the number of forming, i.e., the surface topographies of galvanized steels are roughened in SMF. Moreover, GI steel has a better ability of damage-resistance than GA steel. The mechanisms of topography evolvement are different in the forming of GI and GA steels. Scratch is the main form of surface damage in the forming of GI steels. The severity of scratch can be decreased by increasing die hardness. GA steel results in exfoliating of the coating firstly and then severe scratching. The surface topography of galvannealed steels can be improved by increasing die hardness. However, the hardness should not be too high.